The Relationship between the Use of Pyramid Hologram Media and Student Activities in Science Learning in Elementary Schools - Efrida Yuslia Nurrafiah; M Jaya Adi Putra; Zufriady Zufriady (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this study was to determine whether there was a positive and significant relationship between the use of pyramid hologram media and student activity in science learning in elementary schools. The 4C class research sample consisted of 28 students selected using random sampling techniques.  The type of research conducted is quantitative with a correlational model.  Research data collection techniques use observation and questionnaires. While the instruments used are observation sheets and questionnaires. Data analysis techniques use statistical analysis through product moment correlation tests. Based on the results of the study, with a significant value of 0.031 0.05, it shows that there is a positive and significant relationship between the use of pyramid hologram media and student activity in science learning in elementary schools.